2020
DOI: 10.1186/s12866-020-01827-2
|View full text |Cite
|
Sign up to set email alerts
|

Vital members in the gut microbiotas altered by two probiotic Bifidobacterium strains against liver damage in rats

Abstract: Background: Probiotics are effective to rectify the imbalanced gut microbiota in the diseased cohorts. Two Bifidobacterium strains (LI09 and LI10) were found to alleviate D-galactosamine-induced liver damage (LD) in rats in our previous work. A series of bioinformatic and statistical analyses were performed to determine the vital bacteria in the gut microbiotas altered by the LI09 or LI10 in rats. Results: Two groups of representative phylotypes could distinguish the gut microbiotas of LI09 or LI10 groups from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Bacteroides have gained increasing attention because of their potential regulatory roles in liver diseases, such as NASH and alcoholic hepatitis. 48 , 49 Mice from the Jackson Laboratory (JAX) are more sensitive to ConA-induced liver injury than mice from Taconic Farms (TAC). The abundance of intestinal Bacteroides in JAX mice is significantly lower than TAC mice.…”
Section: Discussionmentioning
confidence: 99%
“…Bacteroides have gained increasing attention because of their potential regulatory roles in liver diseases, such as NASH and alcoholic hepatitis. 48 , 49 Mice from the Jackson Laboratory (JAX) are more sensitive to ConA-induced liver injury than mice from Taconic Farms (TAC). The abundance of intestinal Bacteroides in JAX mice is significantly lower than TAC mice.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that probiotics were able to effectively rectify the imbalanced gut microbiota in the diseased cohorts. 63 In several contexts, fiber consumption was associated with beneficial effects. 14…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that probiotics were able to effectively rectify the imbalanced gut microbiota in the diseased cohorts. 63 In several contexts, fiber consumption was associated with beneficial effects. 14 Therefore, it could be speculated that SCTPII could regulate the relative abundance of beneficial bacteria, such as increasing Lactobacillus, Bacteroides, Akkermansia and other beneficial bacteria in the intestinal tract of immunosuppressed mice and reducing Prevotellacese_UCG-001, Proteus, Alistipes and other harmful bacteria to improve intestinal immunity and alleviate damage from cyclophosphamide.…”
Section: Papermentioning
confidence: 99%
“…Partition Around Medoids clustering analysis has been used to cluster the bacterial communities in different disease studies ( 16 18 , 50 , 51 ). In the present study, the OP microbiotas of both H7N9 and healthy cohorts were clustered into two clusters by PAM analysis.…”
Section: Discussionmentioning
confidence: 99%